Preparation, and ex vivo and in vivo Characterization of Favipiravir-Loaded Aspasomes and Niosomes for Nose-to-Brain Administration - Salamah M; Volk B; Lekli I; Bak I; Gyöngyösi A; Kozma G; Kónya Z; Szalenkó-Tőkés Á; Kiricsi Á; Rovó L; Balogh-Weiser D; Zupkó I; et al. (International Journal of Nanomedicine)
Maryana Salamah,1,2 Balázs Volk,3 István Lekli,4 István Bak,4 Alexandra Gyöngyösi,4 Gábor Kozma,5 Zoltán Kónya,5 Ágnes Szalenkó-Tőkés,6 Ágnes Kiricsi,6 László Rovó,6 Diána Balogh-Weiser,7,8 István Zupkó,2 Ildikó Csóka,1 Gábor Katona,1,* György Tibor Balogh9,10,* 1Institute of Pharmaceutical Technology and Regulatory Affairs, Faculty of Pharmacy, University of Szeged, Szeged, Hungary; 2Institute of Pharmacodynamics and Biopharmacy, Faculty of Pharmacy, University of Szeged, Szeged, Hungary; 3Directorate of Drug Substance Development, Egis Pharmaceuticals Plc., Budapest, Hungary; 4Department of Pharmacology, Faculty of Pharmacy, University of Debrecen, Debrecen, Hungary; 5Faculty of Science and Informatics, Department of Applied & Environmental Chemistry, University of Szeged, Szeged, Hungary; 6Department of Oto-Rhino-Laryngology and Head-Neck Surgery, University of Szeged, Szeged, Hungary; 7Department of Organic Chemistry and Technology, Faculty of Chemical Technology and Biotechnology, Budapest University of Technology and Economics, Budapest, Hungary; 8Department of Physical Chemistry and Materials Science, Faculty of Chemical Technology and Biotechnology, Budapest University of Technology and Economics, Budapest, Hungary; 9Department of Pharmaceutical Chemistry, Semmelweis University, Budapest, Hungary; 10Center for Pharmacology and Drug Research & Development, Department of Pharmaceutical Chemistry, Semmelweis University, Budapest, Hungary*These authors contributed equally to this workCorrespondence: Gábor Katona, Institute of Pharmaceutical Technology and Regulatory Affairs, Faculty of Pharmacy, University of Szeged, Eötvös Str. 6, Szeged, H-6720, Hungary, Email katona.gabor@szte.hu György Tibor Balogh, Department of Pharmaceutical Chemistry, Semmelweis University, Hőgyes Endre Str. 9, Budapest, H-1092, Hungary, Email balogh.gyorgy.tibor@semmelweis.huPurpose: The present study aimed to develop and compare the intranasal applicability of favipiravir-loaded aspasomes (FAV-ASPs) using film hydration method, and favipiravir-loaded niosomes (FAV-NIOs) using ethanol injection method.Methods: The FAV-ASP and FAV-NIO formulations were characterized according to nanoparticulate characteristics (DLS, drug loading, drug encapsulation efficacy, droplet size distribution), drug release and permeability behavior.Results: The optimized FAV-ASP formulation (FAV-ASP8) consisted of FAV, ascorbyl palmitate, Span® 60 and cholesterol (30:25:25:50 w/w) with nano-scale size range (292.06 ± 2.10 nm), narrow polydispersity index (PDI) value (0.36 ± 0.03), adequate zeta potential (− 74.73 ± 3.28 mV) and acceptable encapsulation efficiency (55.33 ± 0.41%). The optimized FAV-NIO formulation (FAV-NIO9) contained FAV, Span® 60 and cholesterol (30:30:40 w/w) with nano-scale size range (167.13 ± 1.60 nm), narrow PDI value (0.07 ± 0.01), adequate zeta potential (− 27.1 ± 1.24 mV) and acceptable encapsulation efficiency (51.30 ± 0.69%). FAV-ASP8 and FAV-NIO9 were suitable for spraying into the nasal cavity (droplet size distribution < 200 μm). In vitro drug release and permeability studies demonstrated enhanced solubility and increased blood–brain barrier (BBB) permeability of FAV formulations, respectively. The ex vivo human nasal permeability study revealed that FAV diffusion from FAV-ASP8 was higher than from FAV-NIO9 or initial FAV. Furthermore, the in vivo animal study showed that FAV-ASP8 had a higher BBB penetration compared to FAV-NIO9 and pure FAV. The in vitro–in vivo correlation study showed good correlation between the in vitro and the in vivo pharmacokinetic data.Conclusion: FAV-ASP8 for nose-to-brain delivery system could be a promising formulation to improve FAV bioavailability compared to FAV-NIO9. Keywords: aspasomes, niosomes, favipiravir, nose-to-brain delivery, ex vivo nasal permeability, in vivo nasal permeability